Тhe influence of natural biostimulants on adaptive state, growth and yield of pea plants under semiarid condition - Kolesnikov, Maksym; Колесніков, Максим Олександрович; Колесников, Максим Александрович; Paschenko, Yuliia; Пащенко, Юлія Петрівна; Пащенко, Юлия Петровна; Kolesnikova, A. (ХНУ ім. В.Н. Каразіна, 2018)
EN: The major legumes culture in Ukraine is peas (Pisum sativum L.) and it has great food value, considerable crop area of which are in the steppe semiarid zone. Peas are very demanding culture and often doesn’t realize it’s genetic productivity potential because of unavailable environmental conditions (Kaminskyi, 2000). Similar conditions change photosynthetic processes, water and mineral status, inhibit development and growth of plants. One of the way to improve plant resistance is the use of natural growth regulators. According to some authors, the growth regulators’ treat contributed to a significant increase of symbiotic nitrogen fixation activity and association. It is proven the efficiency of bio-stimulants Rehoplant, Stympo usage while wheat, barley, lupin, soybeans growing (Ponomarenko, 2010; Pyda, 2013; Buriak, 2015). The aim of the work was to determine the influence of separate and combined application of biostimulants («Stimpo», «Regoplant») and bioactivators («Azotofit», «Rhyzohumin») on the peas pro- antioxidative state, photoassimilation apparatus, yield formation under the semiarid conditions. UK: Використання біопрепаратів підвищує стійкість зернобобових до арідних умов Південного степу України та є перспективним. В роботі показано, що біостимулятори («Стимпо» та «Регоплант») як при роздільному так й при сумісному використанні з «Азотофітом» або «Різогуміном» посилювали адаптаційний статус рослин гороху шляхом стимуляції антиоксидантної системи. За дії біопрепаратів в ризосфері кореневої системи гороху утворювалась більша кількість кореневих бульбачок. Сінергістичний ефект при сумісному використанні біостимуляторів спостерігали під час формування фотоасиміляційного апарату посівів гороху. Біологічна врожайність посівів гороху в роки досліджень за сумісної дії біостимуляторів збільшувалася на 10-16% порівняно з варіантами де застосовували стимулятори окремо.
Вплив природних біостимуляторів на адаптивний стан, ріст та врожайність рослин гороху в семиарідних умовах
Keywords: biostimulants; pea plants; біопрепарати; зернобобові